ANALISIS KEMAMPUAN BERPIKIR KREATIF DALAM PENGERJAAN SOAL ESAI BERBASIS HOTS PADA HASIL TES BAHASA INDONESIA - Nurwahidah, Lina Siti; Kartini, Ari; Asiah, Lisantika Nur (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The 2013 Curriculum of Indonesia mandates various concepts that must be applied through policies and practices by the related parties. Some of them are the implementation of scientific approach and HOTS-based evaluation in the teaching and learning process. The aims of this research are (1) to describe the form of daily Indonesian language HOTS-based test questions; (2) to describe the results of students' creative thinking abilities; (3) to describe the level of difficulty of the daily Indonesian language HOTS-based test questions. This study employed a descriptive method with qualitative analysis techniques. The population of this study was 30 students of class XI IPA SMA Muhammadiyah Cibiuk Garut, while the sample was 20 students who were selected by random sampling technique. The data collection technique was carried out with documentation techniques by analyzing both the test items and the answers. The results show: (1) the daily Indonesian language test items are not completely HOTS-based. (2) not all of the test items meet the creative thinking indicators. (3) there are test items that are not suitable with the difficulty level. In the test items of making proposal chapter, out of five questions, two of them were considered too easy, because of that the questions were not suitable to use in HOTS-based test. From the results of the research above, the implementation of HOTS in test requires a lot of efforts from both the teachers and students. Even though the created test items have been considered at the HOTS level, if they do not assist the students in thinking creatively, then the questions cannot be considered to be able to encourage creative thinking process.